2019
DOI: 10.7759/cureus.4757
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Granulomatous Invasive Fungal Sinusitis in Patients with Clinical Suspicion of Chronic Fungal Rhinosinusitis

Abstract: Introduction One of the common causes of chronic sinusitis is a fungal infection, and there are various types of fungal rhinosinusitis (FRS). Missed diagnosis of occasional granulomatous invasion of fungal sinusitis can lead to involvement in the central nervous system. The aim of this study is to determine the frequency of granulomatous invasive fungal sinusitis (GIFS) in patients with clinical suspicion of chronic FRS. Methods We conducted a descriptive cross-sectional study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(20 reference statements)
1
5
0
Order By: Relevance
“…In our study, the mean age of patients with FRS was 32.8±14 years. This is in concordance with the literature showing majority cases of FRS in the third and fourth decades of life [ 6 , 10 , 15 ]. Our study showed males, 84 (57.53%), to be predominantly affected by FRS.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the mean age of patients with FRS was 32.8±14 years. This is in concordance with the literature showing majority cases of FRS in the third and fourth decades of life [ 6 , 10 , 15 ]. Our study showed males, 84 (57.53%), to be predominantly affected by FRS.…”
Section: Discussionsupporting
confidence: 93%
“…GCIFR is an uncommon disease mainly caused by Aspergillus flavus infection with geographic predilection towards Sudan, India, Pakistan, and Saudi Arabia, with few cases reported in North America and none reported in Mexico ( Table 1 ) [ 3 , 8 ]. Its prevalence among individuals with clinical suspicion of fungal rhinosinusitis has been reported in approximately 20% in subtropical populations, unlike North America, with a prevalence of 0.5% [ 8 , 9 ]. This distinction is attributable to tropical climate, which gives a microaerophilic sinus environment and promotes the growth of A. flavus [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 3 entities AIFS is certainly the most well described, and CGIFS seems to be geographically isolated to the Sudan, Pakistan, and India 2,5,6 . Numerous studies have described AIFS as that with an aggressive disease process and poor survivorship 17‐22 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, CIFS also differs from chronic granulomatous invasive fungal sinusitis (CGIFS) in that there are no granulomas seen on histopathology. Further, most cases of CGIFS have been described in immunocompetent patients from the Sudan, Pakistan, and India, whereas this geographic bias has not been seen in CIFS 2,5 . However, as compared to AIFS in particular, the clinical outcomes of CIFS have been less well described.…”
mentioning
confidence: 99%